Food Safety Management System in Edible Bird’s Nest Industry: A Review - Siti Gusti Ningrum (Journal of Applied Veterinary Science And Technology, 2023)
Background: Food safety management systems such as ISO 22000:2018 have many advantages in solving this newcomer industry's problems. It has enabled the edible bird’s nest industry to plan, implement, operate, maintain, and update an FSMS providing edible bird’s nest products and safe services. Purpose: This review article delineates the role of the food safety management system (FSMS) in improving quality control, production performance, and economic effects in the edible bird’s nest industry. Method: This study was a literature review that collected  sources from books and journals. Results: Hence, the evaluation and assessment could be adequate to meet regulatory food safety requirements. FSMS possess division properties such as quality control, production, marketing, purchasing, general affair, human resources, warehouse, and maintenance. They also have veterinary control numbers and animals quarantine installation, enhancing the edible bird’s nest industry's overall quality control and production performance in Indonesia. Conclusion: The findings of the current review depicted the tremendous potential of cleaning development, which could be explored with the recent advancements in science and technology. The advantages of compelling communication of food safety issues from the FSMS ensure that the edible bird’s nest industry conforms to its stated food safety policy and relevant interested parties in fulfilling the trade requirements set by the export/importing destination country.